Environmental Media as a Learning Resource to Improve 3RD Grade Mathematics Learning Understanding of Students Elementary School - Purwanti, Sri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study was to improve mathematics learning outcomes through environmental media (sticks, pebbles, and candy) in grade 3 students at SD Negeri 2 Winong Boyolali in the even semester of 2022. This research was a classroom action research carried out in 2 cycles. The research subjects were grade 3 students at SD Negeri 2 Winong Boyolali. Sources and research data come from teachers, students, motivation to learn mathematics, and documents learning mathematics. Data collection techniques used are observation, documents, and tests. The results showed that there was an increase in the understanding of multiplication and division in mathematics lessons through the media of sticks, pebbles and candies. This is evidenced by an increase in the learning average starting from the Pre-Cycle, Cycle I, and Cycle II. Based on this, it can be concluded that environmental media can improve students' mathematics learning outcomes.